Multi Patronage and Melting-Pot Social Cleavage: Secularist Political Parties Defeat Islamist Political Parties in Muslim Society - Wawan Edi Kuswandoro (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
A partisan affiliation built from social basic and social cleavage in a relationsip of political parties and civil society as mostly discussed, found its new trend to be endshown by local political practices. This study examined why secularist political parties defeat Islamic political parties in muslim society. This study applicate phenomenology to investigate patronage and clientelism relationship between political parties and societies in research area of Probolinggo, East Java. This study had explored four findings, firstly, weakening of support from traditional Muslim societies with Nahdhatul Ulama (NU) affiliated, called nahdhiyyin, to Islamic parties and the tendency to support secularist parties particularly to PDIP. Secondly, multi patronage phenomena and diversed clientelism which weakens nahdliyin support to Islamic party and crossing over of political support to secularist parties. Thirdly, personal politics from local strong man effect shaped multi patronage and divergent clientelism as well as ends partisan affiliation. Fourthly, social basic had no longer a linear relationship to political parties hence social cleavage faded into new shape, is a melting-pot social cleavage. These findings point out weakening of social basic of Islamic political parties, as irrelevantly political party relationship with social basic to support electoral capacity.